1996
DOI: 10.1007/s002800050416
|View full text |Cite
|
Sign up to set email alerts
|

Dependence of fluorodeoxyuridine-induced cytotoxicity and megabase DNA fragment formation on S phase progression in HT29 cells

Abstract: The relationship between cell cycle progression and induction of DNA double-strand breaks and cytotoxicity by exposure to fluorodeoxyuridine (FdUrd) was studied in HT29 human colon cancer cells. Fractionation of drug-treated populations by centrifugal elutriation yielded subpopulations having widely divergent abilities to progress through S phase in the presence of the drug. One of these subpopulations, which appeared to undergo coordinated growth arrest, was resistant to FdUrd cytotoxicity and DNA damage. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

1999
1999
2012
2012

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 9 publications
(15 reference statements)
0
7
0
Order By: Relevance
“…Replication fork collapse has been proposed before as the mechanism behind double-strand DNA breaks caused by uracil misincorporation and subsequent excision. 35,46 We would like to extend this argument and propose that replication fork collapse is the process behind chromosomal fragmentation after any type of DNA damage, as long as the DNA lesions are repaired via excision. In this respect, replication fork collapse is likely to be the major source of chromosomal fragmentation in the wildtype cells, growing under a variety of conditions.…”
Section: Discussionmentioning
confidence: 97%
“…Replication fork collapse has been proposed before as the mechanism behind double-strand DNA breaks caused by uracil misincorporation and subsequent excision. 35,46 We would like to extend this argument and propose that replication fork collapse is the process behind chromosomal fragmentation after any type of DNA damage, as long as the DNA lesions are repaired via excision. In this respect, replication fork collapse is likely to be the major source of chromosomal fragmentation in the wildtype cells, growing under a variety of conditions.…”
Section: Discussionmentioning
confidence: 97%
“…However, it is not known whether these lesions are substrates for other repair pathways that could productively repair them. Nor is it known whether attempted repair and/or replication of these lesions creates DNA damage that is more toxic, a possibility, considering that FdUrd induces double-strand DNA breaks (Yoshioka et al, 1987;Tang et al, 1996;Meyers et al, 2001). Finally, it is not clear whether PARP inhibition, which disrupts DNA repair, alters the lesions that are ultimately induced by FdUrd.…”
Section: Discussionmentioning
confidence: 99%
“…Our results also demonstrate that these repair pathways do not make lesions induced by FdUrd alone or FϩA more toxic. Given that FdUrd activates ATM and causes DSBs (Yoshioka et al, 1987;Tang et al, 1996;Meyers et al, 2001;Parsels et al, 2004;Wilsker and Bunz, 2007;Liu et al, 2008;Jardim et al, 2009;Geng et al, 2011; and given that FϩA induces more H2AX phosphorylation than FdUrd alone (see Fig. 1B), we were surprised that depletion of ATM or KU80, two proteins that participate in signaling from and repair of DSBs, did not affect the survival of cells treated with these agents.…”
Section: Downloaded Frommentioning
confidence: 99%
“…Responses that involve regulation of cell cycle progression and apoptosis are particularly important in this regard (5,6,21). In previous studies in which we compared the effects of FdUrd in two human colorectal tumor cell lines (HT29 and SW620), we found that the propensity of HT29 cells to try to advance through the cell cycle during profound thymidylate synthase inhibition correlated closely with their sensitivity to FdUrd-induced clonogenic death, relative to SW620 cells (22)(23)(24). Based on these observations, we hypothesized that the sensitivity of HT29 cells to thymidylate synthase inhibition may be due in part to a defect in their cell cycle checkpoint response(s) to FdUrd-induced DNA damage.…”
Section: Introductionmentioning
confidence: 99%